Road cycling and bone health: a scoping review - Short, M.; Heron, N.; Matthews, M. (Journal of Science and Cycling, 2022)
Introduction In competitive road cycling, low body mass is a common focus for many athletes. Due to the high energy expenditure and non-weight bearing nature of competitive road cycling, there are associated health risks including relative energy deficiency and low bone mineral density. Untreated, this can lead to an increased susceptibility to fracture. This can be a particular problem in competitive road cycling where the prevalence of falls is high.